Extracellular heat shock proteins in cancer: From early diagnosis to new therapeutic approach. (November 2022) - Caruso Bavisotto, Celeste; Marino Gammazza, Antonella; Campanella, Claudia; Bucchieri, Fabio; Cappello, Francesco
Abstract: In cancer, human cells lose the ability to properly control the series of events that occur constantly during cell growth and division, including protein expression, stability, and dynamics. Heat shock proteins (Hsps) are key molecules in these events, constitutively expressed at high levels and could furthermore be induced by the response to cancer-induced stress. In tumor cells, Hsps have been shown to be implicated in the regulation of apoptosis, immune responses, angiogenesis and metastasis; in some cases, they can be overexpressed and dysregulated, representing important cancer hallmarks. In the past few years, it has been demonstrated that Hsps can be released by tumor cells through several secreting pathways, including the extracellular vesicles (EVs), thus modulating the tumor microenvironment as well as long-distance intercellular communication and metastatization. In this review, we discuss the role of extracellular Hsps in cancer, with a particular interest in Hsps in EVs. We would also like to highlight the importance of fully understanding of the role of extracellular Hsps released by EVs and encourage further research in this field the use of Hsps as early cancer biomarkers and therapeutic targets.